STRATEGI PEMENANGAN CALEG DALAM PEMILU LEGISLATIF 2019 (Studi Kasus : Kemenangan Danie Budi Tjahyono di Dapil I Provinsi Jawa Tengah) - Kuncoro - Puspito; Turtiantoro - - (Journal of Politic and Government Studies, 2021)
This study discusses the political strategy in the victory of Danie Budi Tjahyono, a legislative candidate in the 2019 election. The aim is to find out how the winning strategy applied by Danie Budi Tjahyono in the Legislative Election of Central Java Province, and find out how the obstacles and challenges faced so that in the end Danie Budi Tjahyono can win a seat in the Regional Representative Council 1 of the Central Java Province. This research uses a case study approach. Data was collected through interviews with Danie Budi Tjahyono, Winning Teams Team, and the public, as well as document searches. The results of this study found that Danie Budi Tjahyono's political journey was not easy because he ran with unemployment status when he was still a legislative candidate. Danie Budi Tjahyono named his winning strategy the “Sweeping Mines” strategy by drawing votes from the public who were offended by the promises of the previous legislative candidates. In addition, Danie Budi Tjahyono ran as a legislative candidate with very little economic capital and with the belief that he could win a seat in the Java DPRD